Comparative Study of Islamic Legal Systems in the Application of the Istishna' Agreement in Indonesia and Malaysia - Tazkiya, Khansa; Harahap, Burhanudin; Purwadi, Hari (NAJAHA, 2022)
The provisions in the Qur'an and al-Hadith bind Islamic Contract Law. From the Islamic perspective, contracts are better known by the word Akad. The most significant factor in the increase in profit power in Islamic contract law is obtained from financing agreements. Indonesia and Malaysia, as Muslim-majority countries, provide different arrangements regarding istishna's financing agreement'. Therefore, this legal research aims to compare Islamic legal systems in applying the istishna' agreement in Indonesia and Malaysia based on the DSN MUI Fatwa and the SAC BNM Fatwa. The research method is a doctrinal legal research method with a comparative approach. The results showed that in the application of the istishna' contract in Indonesia and Malaysia, there was no significant difference. The development of istishna' agreements between the two countries from year to year has fluctuated. The number of istishna' financing agreements in Indonesia is higher than in Malaysia.